Interaction strength varies in relation to tidal gradient and spatial heterogeneity in an intertidal Southwest Atlantic estuarine food web - Alvarez, María Fernanda (2013)
Interaction strength is a key component in food-web dynamics being highly variable over time and space, de- pending on biotic and abiotic conditions. Intertidal soft bottom ecosystems are essential nursery and feeding sites for migratory shorebirds and marine fishes, which in turn affect infaunal assemblage and the food web dy- namic. In these systems, organisms that modify the resource availability to other species (i.e. burrowing crabs) are expected to have significant consequences on infauna distribution and the interactions among organisms. Here we simultaneously evaluated the interaction strength of birds and fishes on infaunal prey in areas with and without crab bioturbation. Field experiments showed weak predator-prey interactions of both predators; however, birds exerted high impact on meiofauna inside bioturbated areas during thewarmseason. Moreover, the effect of fishes differed depending on bioturbation and another factor such as climatic events (e.g. El Niño Southern Oscillation (ENSO)). Thus, our results suggest that interaction strength of birds and fishes on prey are context dependent, varying between different areas, tidal time exposition, ENSO episode and seasons. Also, our results exemplify how the outcome of predator-prey interaction strength can depend on other factors such as the activity of other species that modify the environment.